2000
DOI: 10.1038/sj.gt.3301236
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of integrin-dependent adhesion and survival of endothelial cells by recombinant adenovirus expressing isolated β integrin cytoplasmic domains

Abstract: We explored the possibility of using a genetic approach to inhibit integrin-mediated endothelial cell adhesion and survival. We constructed recombinant adenoviruses (Ads) expressing chimeric proteins consisting of the cytoplasmic and transmembrane domains of integrin ␤1 (CH1), ␤3 (CH3) or the ␤1 transmembrane domain alone (CH2) connected to the extracellular domain of L3T4 placed under the control of the CMV promoter (AdCMV) or the endothelial cell specific Tie-1 promoter (AdTie). All constructs were expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…The rapid degradation of integrin ␤1 suggests that the trigger for endothelial cell death induced by gingipains might be the loss of integrin signaling, which occurs prior to cell detachment and apoptosis. This would be consistent with a recent report demonstrating that disruption of focal adhesions and the actin cytoskeleton by overexpression of integrin ␤1 cytoplasmic domains preceded cell detachment and was, therefore, the cause rather than a consequence of endothelial cell detachment (53). Furthermore, it has been demonstrated that ligation of integrin ␤1 by antibodies protected fibroblasts from apoptosis through upregulation of phosphatidylinositol 3-kinase and Akt/protein kinase B activity (66) and that Akt is deactivated in both caspase-dependent and caspase-independent cell death in several cell types (46).…”
Section: Discussionsupporting
confidence: 80%
“…The rapid degradation of integrin ␤1 suggests that the trigger for endothelial cell death induced by gingipains might be the loss of integrin signaling, which occurs prior to cell detachment and apoptosis. This would be consistent with a recent report demonstrating that disruption of focal adhesions and the actin cytoskeleton by overexpression of integrin ␤1 cytoplasmic domains preceded cell detachment and was, therefore, the cause rather than a consequence of endothelial cell detachment (53). Furthermore, it has been demonstrated that ligation of integrin ␤1 by antibodies protected fibroblasts from apoptosis through upregulation of phosphatidylinositol 3-kinase and Akt/protein kinase B activity (66) and that Akt is deactivated in both caspase-dependent and caspase-independent cell death in several cell types (46).…”
Section: Discussionsupporting
confidence: 80%
“…Established in adhesion-suspension assays for the examination of the cell detachment-related cell death type, termed anoikis (Martin and Vuori, 2004), the prosurvival function of specific integrin subunits such as b1 and b3 is well known (Oguey et al, 2000). In contrast to these acute and transient adhesion-and spreading-related processes, the role of b1-integrin and its downstream signaling in matrix adhered and exponentially growing cells is still unsolved in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Additional targets of this type may explain why such a striking detachment phenotype was observed with such modest decreases in surface ␣3␤1. The degradation of integrins followed by cell detachment may cause some form of apoptosis, a phenomenon observed with integrin ␣5 subunit (39). This detachment-mediated apoptosis, termed anoikis (12,16,46), has been observed in other types of virus infections (45,52,54).…”
Section: Discussionmentioning
confidence: 99%